Creating a Course on Scientific Writing and Oral Presentation in English for Engineering and Science Graduate Students at an Elite Chinese University - John B. Troy; Pei-Ji Liang (Cranmore Publishing, 2021)
The training of non-native English speakers in professional communication in English is a challenge faced in many fields. Herein we describe a course that we have developed to enhance writing and oral communication proficiency for early stage science and engineering Ph.D. students in this area. The course has been taken by approximately 750 students and has received generally favorable reviews. We have focused on the professional needs of our target audience, seeking to train them in how to write scientific journal articles efficiently, and how to generate attractive and clear posters for or give strong oral presentations at scientific conferences. Necessarily, these goals require some consideration of language skills like grammar, syntax and style, but scientific writing places a premium on conciseness and students need to learn how to tell a compelling story within the rigid constraints placed upon them by the structure of a scientific research paper. Our course is built around a series of lectures complemented with small tutorial groups where much of the learning takes place. We probe for improvement in student understanding throughout the course, thus permitting us to make minor adjustments if needed as we proceed. While this course was designed for science and engineering graduate students we believe that its format should be easily adaptable to satisfy the needs of other professions.